Deficits in implementing integrated water resources management in South Africa: The role of institutional interplay. Issue 136 (October 2022) - Lukat, Evelyn; Pahl-Wostl, Claudia; Lenschow, Andrea
Abstract: Integrated Water Resources Management (IWRM) has been transferred from the Global North to the Global South. Decades after adopting IWRM in formal policies, countries in the Global South in particular are struggling to implement it in practice. We believe the interplay of formal and informal institutions to be a reason for the failed transfer, but institutional interplay is rarely considered when policies are transferred. Based on a case study of water governance in the uMngeni river basin in South Africa, we investigate how specific types of informal institutions affect the practical implementation of selected aspects of IWRM: subsidiarity, stakeholder involvement, and securing access to water and sanitation. We explore (1) informal institutions that supported previous formal legislation and are still actively reproduced, (2) bureaucratic cultures operationalised through governance modes, and (3) traditional governance as part of a dual governance system. We find that in most cases, a higher level of similarity between formal and informal institutions leads to the more frequent implementation of formal provisions, and hence converging interplay between institutions. Passed-down power structures, another aspect of informal institutions, proved particularly resistant to institutional change. We conclude that analysing the setting of informal institutions before making policy reforms would provide a more realistic assessment of the results to be expected. Understanding institutional interplay in policy transfer processes is hence essential to designing more effective policies and avoiding the pitfalls inherent to blueprint solutions. Highlights: Institutional interplay is one cause of slow IWRM implementation in the Global South. Complementary informal and formal institutions support policy implementation. Passed-down power structures are particularly resistant to institutional change. Considering informal institutions is recommended when designing place-based policies.